2021
DOI: 10.1007/s00127-021-02155-0
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic relationship between hearing loss, quality of life, socioeconomic position and depression and the impact of hearing aids: answers from the English Longitudinal Study of Ageing (ELSA)

Abstract: Purpose The adverse impact of hearing loss (HL) extends beyond auditory impairment and may affect the individuals' psychosocial wellbeing. We aimed to examine whether there exists a causal psychosocial pathway between HL and depression in later life, via socioeconomic factors and quality of life, and whether hearing aids usage alleviates depressive symptoms over time. Methods We examined the longitudinal relationship between HL and depressive symptoms (CES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
1
19
2
Order By: Relevance
“…Recent evidence suggests that hearing rehabilitation may not only improve hearing ability and quality of life but can also have beneficial effects on depression. For example, naturalistic studies of neuropsychiatric status have shown depressive symptom improvement after treatment with both hearing aids and cochlear implants 11‐13 . One study comparing hearing treatment to a wait list control group observed increased self‐reported quality‐of‐life and decreased depressive symptoms post hearing aid prescription, 14 but wait list groups are in general weak controls that may result in an overestimation of treatment effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that hearing rehabilitation may not only improve hearing ability and quality of life but can also have beneficial effects on depression. For example, naturalistic studies of neuropsychiatric status have shown depressive symptom improvement after treatment with both hearing aids and cochlear implants 11‐13 . One study comparing hearing treatment to a wait list control group observed increased self‐reported quality‐of‐life and decreased depressive symptoms post hearing aid prescription, 14 but wait list groups are in general weak controls that may result in an overestimation of treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, naturalistic studies of neuropsychiatric status have shown depressive symptom improvement after treatment with both hearing aids and cochlear implants. [11][12][13] One study comparing hearing treatment to a wait list control group observed increased self-reported quality-of-life and decreased depressive symptoms post hearing aid prescription, 14 but wait list groups are in general weak controls that may result in an overestimation of treatment effects. A recent randomized controlled trial found improvement in depressive symptoms after 4-week of aural rehabilitation, 15 but did not select participants with clinically significant depressive symptoms, thus limiting the generalizability of such results to a population with MDD.…”
mentioning
confidence: 99%
“…HL can cause many problems, and communication barriers that accompany HL may lead to disability and psychological inferiority, which results in lower self-esteem and even worsen mental health [ 25 , 26 ]. At the same time, a recent study also found a longitudinal relationship between HL and depression [ 27 ].…”
Section: Introductionmentioning
confidence: 92%
“…A recent study showed that older people with severe HL have a 20% increased risk of death compared to people with normal hearing [ 18 ]. In addition, a number of studies have shown that HL has a significant negative impact on the health status, social isolation and physical functions of the older adults [ 19 27 ]. One of the studies presented that HL can also cause communication difficulties, which not only affect work efficiency, but also negatively affect cognition and emotions [ 19 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly among older adults, who may no longer be employed, measures of SEP related to wealth or accumulated assets may be more appropriate than income. For example, in a study assessing the relationship between hearing loss, SEP, and depression using data from the English Longitudinal Study of Aging, SEP was measured by educational level and wealth [16]. In this example, wealth was thought to be the most appropriate indicator for the older adult population's SEP as it also captures retired individuals or those in later stages of active employment [16].…”
Section: Defining Socioeconomic Positionmentioning
confidence: 99%